PERTIMBANGAN HAKIM DALAM MENETAPKAN DISPENSASI NIKAH DI PENGADILAN AGAMA SUNGGUMINASA - Darwis, Sulhah; Sultan, Lomba; Kurniati, Kurniati (Universitas Islam Negeri Alauddin Makassar, 2023)
This article aims to discuss the legal considerations by the judges of the Sungguminasa Religious Court in giving a decision to determine a marriage dispensation application. This paper tries to examine the effectiveness of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning marriage which in general provides legitimacy for the age limit for marriage in Indonesia, which is then collided with a request for dispensation of marriage which some people are of the view is the allowance for the age that has been stipulated in article 7 paragraph (1), this paper then analyzes how single judges examine and assess applications for dispensation of marriage by the community. The type of research used is field research or field with an approach Juridical, namely in accordance with the regulations in force in Indonesia and sociological based on phenomena that occur in society. The main factors that become legal considerations for judges in determining a marriage dispensation application are: Association Factors, Economic Factors, Educational Factors, Environmental Factors and Cultural Factors. These various factors are examined and assessed by the judge in depth while still clearly considering the interests of a child. It is hoped that the judge's decision will provide legal certainty for applicants for marriage dispensation.